The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s41543-017-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Athlete First: a Comprehensive Assessment of Elite Para Athlete Well-Being

Abstract: Our aim was to comprehensively assess the well-being of athletes in Paralympic sports and determine if their results are comparable to other elite athlete populations. Participants (Para, n = 103; Olympic, n = 193; 56% female) were invited to complete an online questionnaire measuring subjective, psychological, social, and physical well-being. Using ANOVA analyses, Para athletes had comparable well-being to Olympic sport athletes across most dimensions. Para athletes recorded significantly lower physical well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
3
6
0
Order By: Relevance
“…While it is understood that more experienced athletes have greater maturity and understanding of life circumstances, younger athletes have been more hopeless about the limitations of confinement. All of this is in line with the hypotheses in studies on psychological well-being among athletes of different ages [16] and sporting experience [52]. Although most of the hypotheses have been confirmed, recent studies have marked the relevance of sports practice for psychological well-being in terms of gender, in favour of men [53], it should be noted that no gender differences have been found between the scores of men and women in this study, although they have shown high indicators of psychological well-being in both subgroups.…”
Section: Discussionsupporting
confidence: 86%
“…While it is understood that more experienced athletes have greater maturity and understanding of life circumstances, younger athletes have been more hopeless about the limitations of confinement. All of this is in line with the hypotheses in studies on psychological well-being among athletes of different ages [16] and sporting experience [52]. Although most of the hypotheses have been confirmed, recent studies have marked the relevance of sports practice for psychological well-being in terms of gender, in favour of men [53], it should be noted that no gender differences have been found between the scores of men and women in this study, although they have shown high indicators of psychological well-being in both subgroups.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have indicated the need for a holistic conceptualization of well-being; as pressures faced outside of sport have an equally great impact on performance and overall well-being for athletes as those experienced within sport (e.g., Dunn, 2014; Galli, 2019; Giles et al, 2020; Lundqvist, 2011; Macdougall, O’Halloran, Sherry, et al, 2017; Macdougall et al, 2015). Within our present study, para-athletes’ conceptualizations of well-being aligned with an integrated approach, acknowledging the impact of broader challenges faced in addition to the sport-specific contextual influences on well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The elite sporting environment is complex and challenging. The unique and contextual physical, mental, and social demands an athlete faces can be beneficial and/or detrimental to their health and well-being (Macdougall, O’Halloran, Sherry, et al, 2017; Rice et al, 2016). How an athlete copes, their mental resilience, and whether they have a strong support network will determine an athlete’s success and impact on their well-being (Mandolesi et al, 2018; Nässi et al, 2017).…”
mentioning
confidence: 99%
“…Other work has compared their mental health to that of other populations including individuals with disabilities who do not participate in para-sport and Olympians (Macdougall et al, 2017;Olive et al, 2021). A growing body of work has also paid attention to the applied practice and the delivery of psychological skills training in para-sport contexts when working with Paralympic athletes (Guerrero et al, 2020).…”
Section: Para-athlete Wellbeingmentioning
confidence: 99%